Porous ZnO nanorod for targeted delivery of doxorubicin: in vitro and in vivo response for therapeutic applications - Mitra, Shouvik; Subia, B.; Patra, Prasun; Chandra, Sourov; Debnath, Nitai; Das, Sumistha; Banerjee, Rahul; Kundu, Subhas C.; Pramanik, Panchanan; Goswami, Arunava (Journal of Materials Chemistry, 2012)
Cancer cell specific targeted delivery (TDD) by porous nanocarrier is on a high role. Here in a simple route for the synthesis of porous ZnO nanorods (ZnO) has been demonstrated. ZnO expressed very high surface area of 305.14 m(2) g(-1) (S-BET) and uniformly distributed pores of 5 nm. In continuation ZnO has been fabricated with 3-aminophosphonic acid followed by folic acid to yield folate conjugated porous ZnO nanorod (ZnO-FA). High surface area, uniformly distributed pores on its surface make the nanocarrier suitable for high drug loading (88%) of the anticancer drug doxorubicin (DOX). A pH triggered drug release was observed with minimum release in pathophysical conditions. In vitro efficacy of DOX loaded ZnO-FA (ZnO-FA-DOX) has been evaluated against breast cancer cells MDA-MB-231, which is not possible alone by DOX or ZnO-FA. Targeted scaffold with pendant -NH2 group has been covalently bonded with fluorescent dye (RITC) for cellular uptake and imaging studies in MDA-MB-231 cells; the possible pathway for cancer regression has also been evaluated. Even in vivo acute and intravenous toxicological evaluation on murine model system complemented biocompatibility of ZnO-FA in TDD. All together we have collaged a template free synthesis of porous ZnO nanorod, successful targeting on to cancer cells, high drug loading, pH triggered drug release, in vitro efficacy of ZnO-FA-DOX against MDA-MB-231 cells and in vivo compatibility as well. We envisioned the future prospect of porous ZnO nanostructures in TDD.

Rapid microwave synthesis of fluorescent hydrophobic carbon dots - Mitra, Shouvik; Chandra, Sourov; Kundu, Tanay; Banerjee, Rahul; Pramanik, Panchanan; Goswami, Arunava (RSC Advances, 2012)
Fluorescent hydrophobic carbon dots (HCDs) have been fabricated from a poloxamer by a simple microwave assisted process within a few minutes for the first time. Small and distinct spherical HCDs emitted bright blue and green fluorescent light depending upon the excitation wavelength and were dispersed easily in a wide variety of organic solvents. HCDs exhibited excellent water resistant behavior with a contact angle of similar to 122 degrees enforcing good hydrophobic character which will be quite useful in potential surface applications.